Kepastian Hukum Akta Jual Beli yang Dibuat Pejabat Pembuat Akta Tanah Mengandung Cacat Secara Materil - Ahmad Chairul Anwar; Anriz Nazarudin Halim; Dhoni Martien (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The phenomenon occurring in society regarding deeds of sale and purchase drawn up by land deed officials that contain material defects is certainly contrary to what is stipulated by law. Thus, the research questions are: What are the legal consequences of a material defect in a Deed of Sale and Purchase drawn up by a Land Deed Official? and How does a material defect in a Deed of Sale and Purchase drawn up by a Land Deed Official arise? In this study, the researcher uses Otto Jan Michael's theory of legal certainty and R. Soeroso's theory of legal consequences. The research method used in this study is normative juridical research janis, namely legal research with literature studies. The research approaches used are legislation, conceptual approach, analytical approach and case approach. The technique of collecting legal materials is by identifying and inventorying positive legal rules. Literature, journals and other sources of legal materials. For the analysis technique of legal materials, it is carried out by grammatical interpretation, systematic interpretation, analogy construction and legal refinement construction. The results of this study found the conclusion that the legal consequences of the sale and purchase deed being carried out unilaterally made before PPAT caused the sale and purchase deed to not have legal certainty. Although the sale and purchase deed was made formally by and before PPAT, the legal action contained a material defect, and was canceled by the court, there was also a legal relationship between the legal subjects, the cancellation showed legal certainty, but gave birth to a lawsuit due to unlawful acts, and the legal certainty of the sale and purchase deed made by PPAT contained material defects making PPAT not have binding legal force which resulted in unilateral The sale of land must be done by mutual agreement or known to both parties, in addition to having no legal force, the deed is canceled by the court. Thus, the cancellation of the sale and purchase deed contains a material defect in the court, providing legal certainty for matters that are not in accordance with the applicable provisions of the law.